IMPLEMENTASI MANAJEMEN STRATEGIK MUTU PENDIDIKAN DALAM PROSES PEMBELAJARAN DI SD TA’MIRUL ISLAM INOVATIF SURAKARTA TAHUN AJARAN 2025/2026 - Mutamakkin Alallah; Syamsul Huda Rohmadi (PT. Hasba Edukasi Mandiri, 2026)
This study aims to examine (1) the implementation of strategic management, (2) the evaluation of the implementation of strategic management of educational quality, and (3) the challenges in implementing strategic management of educational quality in the learning process at SD Ta’mirul Islam Inovatif Surakarta in the 2025/2026 academic year. This research employed a qualitative descriptive approach with a case study design focused on the learning process. The results of the study indicate that the implementation of strategic management of educational quality is carried out through three main stages, namely planning, organizing, and the implementation of learning. (1) The planning stage includes the formulation of the school’s vision and mission, strategic programs, learning tools, and quality support programs. (2) The organizing stage is conducted collaboratively using a constructivist approach. (3) The implementation stage is carried out through preliminary, core, and closing activities in a systematic and innovative manner. Learning evaluation is conducted through academic supervision, evaluation meetings, and analysis of student learning outcomes as a basis for improving the learning process.